Potential determinants of physical inactivity among long-term colorectal cancer survivors - Eyl-Armbruster, Ruth Elisa; Koch, Lena; Jansen, Lina; Walter, Viola; Carr, Prudence R.; Hoffmeister, Michael; Chang-Claude, Jenny; Brenner, Hermann; Arndt, Volker (Journal of cancer survivorship, 2018)
PURPOSE: Since physical activity (PA) has been shown to be associated with better prognosis and quality of life (QOL) in colorectal cancer (CRC) patients, this study focuses on the barriers of PA among CRC survivors. - METHODS: This study is based on a population-based study from Germany of 1343 women and men, diagnosed with CRC between 2003 and 2008 and being alive five years later. Multivariable logistic regression was used to explore associations between baseline as well as five-year follow-up (5YFU) characteristics and physical inactivity (PIA) at 5YFU. Quartiles were calculated based on metabolic equivalent hours per week of PA at baseline and at 5YFU. Participants in quartile 1 were defined as physically inactive, and patients in quartile 2 to quartile 4 were defined as physically active. - RESULTS: Cancer-specific factors such as having a stoma (odds ratio (OR) = 1.51, 95% confidence interval (CI) = 1.12-2.04), demographic factors such as living in a small town or city (OR = 1.46, 95% CI = 1.05-2.02; OR = 1.42, 95% CI = 1.01-2.02), older age (OR = 1.44, 95% CI = 0.80-2.58), or being divorced (OR = 1.72, 95% CI = 0.96-3.07), as well as lifestyle factors such as being a current smoker (OR = 1.54, 95% CI = 1.04-2.29) or being obese (OR = 1.43, 95% CI = 0.96-2.13) were associated with PIA at 5YFU. Subgroup analyses showed that the association between body mass index and PIA was stronger in women than in men. Baseline PA was identified as a strong predictor of PIA at 5YFU. - CONCLUSIONS: Findings suggest that predominately patients with a stoma, patients living in a more populated area, being older, divorced, a current smoker, or obese were more likely to be physically inactive and therefore could be targeted to be more physically active. - IMPLICATIONS FOR CANCER SURVIVORS: Addressing barriers for PA might help to develop specific, individually tailored PA interventions to overcome PIA and improve the long-term outcome of CRC survivors.
Gesehen am 12.11.2018